Molecular characterization and follow‐up of five CML patients with new BCR–ABL1 fusion transcripts. Issue 10 (7th August 2015) - Huet, Sarah; Dulucq, Stéphanie; Chauveau, Aurélie; Ménard, Audrey; Chomel, Jean‐Claude; Maisonneuve, Hervé; Legros, Laurence; Perrin, Marie‐Claire; Ferrant, Emmanuelle; Moreilhon, Chimène; Couturier, Marie‐Anne; Sujobert, Pierre; et al.
<x xml:space="preserve">Abstract</x> We report five chronic myeloid leukaemia (CML) patients in whom we identified and characterized undescribed BCR–ABL1 fusion transcripts. We investigated the precise features of the molecular rearrangements and the minimal residual disease follow‐up for these five patients. Three resulted from new rearrangements between the BCR and ABL1 sequences (the breakpoints being located within BCR exon 13 in two cases and within BCR exon 18 in one case). The other two cases revealed a complex e8‐[ins]‐a2 fusion transcript involving a third partner gene, PRDM12 and SPECC1L, respectively. Moreover, single nucleotide polymorphism‐array analysis performed in the latter two cases showed copy number alterations shared by the two patients, thus identifying genes that were deleted during rearrangement and suggesting their potential role in CML pathogenesis. Interestingly, we highlight that the prognosis of alterations, such as the presence of an e8a2 transcript or the deletion of various genes, which have been controversial, may be definitively erased by the introduction of tyrosine kinase inhibitors (TKIs). © 2015 Wiley Periodicals, Inc.